Structure design of aluminum/CFRP hybrid stringers accounting for multiple impact angles. (1st February 2023) - Wang, Zhen; Zhao, Zhonghao; Chen, Yisong; Wu, Yongqiang; Song, Kai; Zhu, Guohua
Graphical abstract: Highlight: Impacting performances of both single aluminum stringers and aluminum/CFRP hybrid stringers were experimentally and numerically explored. The energy-absorbing mechanisms of aluminum/CFRP hybrid stringers under impact loads were experimentally, numerically and analytically revealed. The crashworthiness and lightweight performances of aluminum/CFRP hybrid stringers were optimized through a multi-objectives discrete optimization method accounting for multiple impact angles. Abstract: Metal/composite hybrid structures exhibit advantages in crashworthiness and lightweightness and have been extended to many fields, including automobile, aerospace, and civil engineering. However, to date, studies on energy-absorbing mechanisms and the design methods of metal/hybrid structures are still insufficient. This study aims to develop an efficient and reliable optimization approach for structural lightweight design of aluminum/CFRP hybrid stringers. Both physical and virtual impact tests of single aluminum stringers and aluminum/CFRP hybrid stringers were carried out. The results show that the total energy absorption of the hybrid stringer are higher than the sum of the single aluminum stringer and the CFRP core. The energy absorption enhancement of the aluminum mainly contributed to the load-carrying improvement of the hybrid stringer because of the reinforcement effects caused by the internal CFRP core. Parametric studies indicate that the crashworthiness performances of the hybrid stringer can be improved by increasing the aluminum thickness, CFRP layer, and foam filling density, but the weight and the cost of the hybrid stringer also increase. The multi-objective discrete optimisation design can provide a cost-efficient approach to better balance the relationships among impact performance and material cost and structure weight for aluminum/CFRP hybrid stringers.